RESOLVING THE MANTLE HE/NE AND CRUSTAL 21NE/22NE IN WELL GASES - Ballentine C.J. (My University, 1997)
He and Ne isotope data from 48 mantle-rich well gases (3He/4He>0.1Ra) in 6 different regions of crustal extension around the world are used to derive both the average mantle He/Ne elemental ratio beneath the extensional systems, and the regional average crustal 21Ne/22Ne nucleogenic production ratio, (21Ne/22Ne)crust. Assuming a mantle with R/Ra=6.0–8.0Ra, on a plot of measured 3He/4He vs. air-corrected 21Ne/22Ne, 44 of the 48 data points fall within error of a well- defined mixing line between mantle and crust isotopic end-member values. The mixing line requires a mantle 3He/22Ne range of 0.6–1.9 and is less than half that estimated for the upper mantle, assuming steady state and a Solar-like lower mantle and . The derived (21Ne/22Ne)crust is 0.47–0.76. This is significantly smaller than the theoretical value of 3.5 [3]. The low (21Ne/22Ne)crust confirms that mineral scale preferential siting of U and Th with respect to O and F controls the regional (21Ne/22Ne)crust[4]. The difference between the derived well-gas mantle He/Ne and estimated upper-mantle values can be reconciled by a gas/melt solubility fractionation process. This requires that the gas/melt volume ratio is small (<0.001) in all of the rifting environments in order to produce the observed magnitude of He/Ne fractionation. These small gas/melt volume ratios can only be produced in the lithospheric mantle. Furthermore, this requires that the mantle He/Ne composition is similar to or less than models invoking a Solar-like upper mantle, with (3He/22Ne)≤4.4. These results are consistent with a model in which small melt fraction asthenospheric melts are emplaced into the subcontinental lithospheric mantle. These melts partially degas, to a similar magnitude in all regions, lose a maximum of ∼15% of their He content by gas/melt phase partitioning, and form the dominant source of mantle-derived volatiles in regions of crustal extension. During migration of the magmatic volatiles through the crust the fractionated mantle-derived gases mix with crustal radiogenic noble gases on a regional scale, at or near their elemental production ratios.